Passive filters allocation in unbalanced distribution network with high penetration of distributed generation - Semensato, Marcelo; Oliveira Rezende, Jaqueline; Antônio Lambert, José (Latin American Journal of Energy Research, 2023)
The purpose of this paper is the allocation of passive filters in an unbalanced power network with high penetration of distributed generation to minimize the costs of power losses in the distribution lines, including power losses caused by harmonic components and neutral conductor power losses due to unbalanced loads. The harmonic components and the fundamental current generated by the distributed generation cause a voltage increase in the generation bus, and the voltages in the network above the limit allowed by standard are reduced by allocating passive filters without cutting the active power in the distributed generation. The unbalance and reactive power compensation is performed by the ideal compensation method applied to the distribution network. The tests are for the IEEE 34 bus network, with the fourth wire in the simulation being the isolated neutral. The scatter search metaheuristic applied in the simulation tends to minimize the costs of power losses in the lines and the costs of the passive filters allocated in the medium voltage distribution network, meeting the operational constraints of the network.
Keywords: Allocation of passive filters; unbalanced distribution network; ideal compensation method; harmonic components; distributed generation